2010
DOI: 10.1177/0898264310366752
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Level and Rate of Change of Physical Function and Grip Strength in the Danish 1905-Cohort Study

Abstract: Objectives-The study was conducted to examine sex differences in the initial level and rate of change in physical function and grip strength.Method-The baseline survey included 2,262 Danes born in 1905 and alive in 1998 and followedup in 2000, 2003, and 2005. Hence, the authors fully used the power of having a cohort with multiple assessments in late life and virtually complete follow-up of lifespan (through December 2008). Latent growth curve modeling was used.Results-Men had higher initial levels and rates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
57
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 61 publications
(87 reference statements)
16
57
1
3
Order By: Relevance
“…In one study that examined this apparent contradiction, the authors hypothesized that men and women differ not only in their initial grip strength levels, but also in the pace at which their grip strength declines with age. Thus, they suggested that the sex-specific associations of these parameters with lifespan may partially explain sex differences in health and mortality (Oksuzyan et al 2010c). The results of the study indicated that men have higher initial levels of and a steeper decline in grip strength, but that the initial level was more strongly associated with lifespan than the age-related decline.…”
Section: Sex Differences In Physical Performance Testsmentioning
confidence: 89%
See 1 more Smart Citation
“…In one study that examined this apparent contradiction, the authors hypothesized that men and women differ not only in their initial grip strength levels, but also in the pace at which their grip strength declines with age. Thus, they suggested that the sex-specific associations of these parameters with lifespan may partially explain sex differences in health and mortality (Oksuzyan et al 2010c). The results of the study indicated that men have higher initial levels of and a steeper decline in grip strength, but that the initial level was more strongly associated with lifespan than the age-related decline.…”
Section: Sex Differences In Physical Performance Testsmentioning
confidence: 89%
“…This finding suggests that age-related declines in functional limitations are likely to be gender-specific. Although less research has been done on sex differences in age-related declines in physical functioning, there is some evidence that the rates of decline in physical functioning are higher among men than among women (Oksuzyan et al 2010c).…”
Section: Sex Differences In Functional Statusmentioning
confidence: 99%
“…For both sexes, initial (absolute) GS was relevant for long-term survival irrespective of baseline physical activity and fat mass. The predictive value of baseline GS for longterm survival in older adults aged ≥85 has been observed previously [16,17]. Despite differences across the studies reviewed, including length of follow-up and selection of confounders, the importance of initial GS (muscle strength) for survival over 7-10 years have been seen in the Leiden 85-plus Study (35% increased risk for those in the lowest sex-specific tertile) [16], and in the Danish 1905-Cohort study (lifespan was positively correlated with the GS intercept in both sexes) [17].…”
Section: Discussionmentioning
confidence: 56%
“…Findings from the studies using the rate of change in muscle strength and physical performance as predictors of mortality have been mixed [13,[16][17][18][19][20][21][22][23]. For example, in the Baltimore Longitudinal Study (BLSA) the rate of change in GS in men aged < 60 was more important for long-term mortality than initial level, whilst for men aged ≥60 higher baseline GS but not slope predicted longer survival over a 40-year period [18].…”
Section: Introductionmentioning
confidence: 99%
“…The age-related decline in grip strength in adults has been reported in a number of previous longitudinal studies 2,20,[36][37][38][39] . However, the trajectory of grip strength with aging has been described as linear 36,40,41) or curved/quadratic 37,42,43) , and some studies have illustrated the slope with flexion points. Based on a Bayesian longitudinal plateau model of adult grip strength, Nahhas et al 44) described the trajectory of grip strength as peaking at 36 years of age for both men and women and then starting to decline at 56 years for men and 50 years for women.…”
Section: Grip Strength and Aging Processmentioning
confidence: 99%